“It’s a change your life kind of program”: A Healing-Focused Camping Weekend for Urban Indigenous Families Living in Fredericton, New Brunswick - Hickey, Jason; Powling, Hayley; McKinney, Patsy; Robbins, Tristin; Carrier, Nathan; Nash, Abigail (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2020)
We present a community-driven research project designed to evaluate an innovative land-based healing initiative – a traditional camping weekend – for urban Indigenous families. The initiative was developed and implemented by Under One Sky Friendship Centre in Fredericton, NB, and involved a weekend-long celebration of culture and community. We gathered data from family members, staff, and stakeholders, and completed a thematic analysis and community review before synthesizing results into a narrative summary. Themes included Skitkəmikw (Land), Cəcahkw (Spirit), Skicinowihkw & Nekwtakotəmocik (Community & Family), and Sakələməlsowakən (Wellbeing). These connections are echoed throughout the article by quotes from participants that capture the essence of the experience. Our research helps to fill a knowledge gap in this area and supports the limited body of existing literature in demonstrating that community-led, land-based healing initiatives support Indigenous wellbeing in many ways that mainstream approaches cannot. Future work is needed to scale up land-based healing initiatives that provide community-led approaches to health promotion, and to examine the effects of ongoing participation on long-term health and wellness outcomes.